Exploitation of Nature in the Novel "The Brave Child" by Tereliye: Ecofeminism Study - Sofiea Anggraini; Filda Fitriani (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Natural resources are very important resources in human life. Humans definitely need natural resources to meet their needs, but currently environmental problems have become a very global phenomenon. Excessive exploitation without good planning will have impacts that can damage the sustainability and balance of the ecosystem of human life. Women have full control over their roles and positions in efforts to prevent or create a beautiful nature. Of course, the relationship between humans and nature gives an idea that nature and humans are basically one unit. Therefore, this theory is able to produce creative ideas in utilizing the beauty of nature. This research discusses the exploitation of nature contained in the novel Si Anak Berberani by Tere Liye using Ecofeminist Studies.